Scientific Opinion on application EFSA‐GMO‐NL‐2016‐132 for authorisation of genetically modified of insect‐resistant and herbicide‐tolerant soybean DAS–81419–2 × DAS–44406–6 for food and feed uses, import and processing submitted in accordance with Regulation (EC) No 1829/2003 by Dow Agrosciences LCC. (20th November 2020) - ; Naegeli, Hanspeter; Bresson, Jean‐Louis; Dalmay, Tamas; Dewhurst, Ian Crawford; Epstein, Michelle M; Firbank, Leslie George; Guerche, Philippe; Hejatko, Jan; Moreno, Francisco Javier; Mullins, Ewen; Nogué, Fabien; et al.
Abstract: Soybean DAS–8419–2 × DAS–44406–6 was developed to provide protection against certain lepidopteran pests and tolerance to 2, 4–dichlorophenoxyacetic acid and other related phenoxy herbicides, and glyphosate‐ and glufosinate ammonium‐containing herbicides. The Genetically Modified Organisms (GMO) Panel previously assessed the two single soybean events and did not identify safety concerns. No new data on the single soybean events, leading to modification of the original conclusions on their safety have been identified. The molecular characterisation, comparative analysis (agronomic, phenotypic and compositional characteristics) and the outcome of the toxicological, allergenicity and nutritional assessment indicate that the combination of the single soybean events and of the newly expressed proteins in the two‐event stack soybean does not give rise to food and feed safety and nutritional concerns. In the case of accidental release of viable DAS–8419–2 × DAS–44406–6 seeds into the environment, soybean DAS–8419–2 × DAS–44406–6 would not raise environmental safety concerns. The post‐market environmental monitoring plan and reporting intervals are in line with the intended uses of soybean DAS–8419–2 × DAS–44406–6. In conclusion, the GMO Panel considers that soybean DAS–8419–2 × DAS–44406–6, as described in this application, is as safe as its conventional counterpart and the non‐genetically modified soybean reference varieties tested with respect to potential effects on human and animal health and the environment.